Spironolactone Improves the All-Cause Mortality and Re-Hospitalization Rates in Acute Myocardial Infarction with Chronic Kidney Disease Patients - Qu, Xiang; Yao, Hui; Chen, Changxi; Kong, Shuting; Sun, Lingyue; Du, Leilei; Liang, Siqi; Gao, Zhan; Zheng, Gaoshu; Zheng, Minghua; Zhao, Chuhuan; Feng, Xiafei; et al. (Frontiers in Pharmacology, 2021)
Background: Mineralocorticoid receptor antagonists (MRA) improve outcomes in chronic kidney disease (CKD) and acute myocardial infarction (AMI) patients. However, the lack of evidence regarding long-term clinical outcomes in the use of MRA, including spironolactone, in patients with AMI combined with CKD. Objectives: This study aimed to investigate whether spironolactone could significantly reduce the risk of all-cause mortality and re-admission in patients with AMI and CKD. Methods: In this single center, observational, retrospective, registry based clinical study, a total of 2,465 AMI patients were initially screened; after excluding patients with estimated glomerular filtration rate more than 60 ml/min/1.73 m2, 360 patients in the standard treatment group and 200 patients in the spironolactone group met the criteria. All enrolled patients follow-up for 30 months. The primary outcomes were all-cause mortality and re-admission. The key safety outcome was hyperkalemia rates during the 30 months follow-up period. Results: 160 (44.4%) and 41 (20.5%) patients in the standard treatment and spironolactone groups died, respectively [hazard ratio (HR): 0.389; 95% confidence interval (CI): 0.276–0.548; p < 0.001]. Re-admission occurred in 217 (60.3%) and 95 (47.5%) patients in the standard treatment and spironolactone groups, respectively (HR: 0.664; 95% CI: 0.522–0.846; p = 0.004). The spironolactone group was divided into two based on the daily dose, low dose group (no more than 40 mg) and high dose group (more than 40 mg); the differences in the mortality rate between low dose group (16.7%) and the standard treatment group (44.4%) (HR: 0.309; 95% CI: 0.228–0.418; p < 0.001) and high dose group (34.1%) (HR: 0.429; 95% CI: 0.199–0.925; p = 0.007) were significant. The differences in re-hospitalization rate between low dose group (43.6%) and the standard treatment group (60.3%) (HR: 0.583; 95% CI: 0.457–0.744; p < 0.001) and high dose group (61.4%) (HR: 0.551; 95% CI: 0.326–0.930; p = 0.007) was significant. Hyperkalemia occurred in 18 (9.0%) and 18 (5.0%) patients in the spironolactone group and standard treatment group, respectively (HR: 1.879; 95% CI: 0.954–3.700; p = 0.068). Whereas, Hyperkalemia occurred in high dose group (20.5%) significantly more often than in the standard treatment group (p < 0.001) and low dose group (5.8%) (p = 0.003). Conclusion: Using MRA, such as spironolactone, may substantially reduce the risk of both all-cause mortality and re-admission in patients with AMI and CKD; the use of low-dose spironolactone has the best efficacy and safety. However, this was a relatively small sample size, single center, observational, retrospective, registry based clinical study and further prospective evaluation in adequately powered randomized trials were needed before further use of spironolactone in AMI with CKD population.